The Relevance of Criteria of Poverty with Household Poverty in South Sumatra - Prihartini, Amelia; Sriati, Sriati; Alamsyah, Alamsyah (Universitas Muhammadiyah Ponorogo, 2025)
The Ministry of Social Affairs of the Republic of Indonesia issued Ministerial Decree No. 262/Huk/2022, outlining the criteria for identifying poverty. This study aims to analyze the relevance of these indigent criteria in the Ministerial Decree to the poverty conditions of households in South Sumatra Province. Poverty status determined by the March 2023 poverty line, as reported by the Central Bureau of Statistics (BPS). Using data from the March 2023 National Socioeconomic Survey (Susenas), a sample of 11,070 households was analyzed through univariate, bivariate, and multivariate approaches. The results indicate that seven out of the eight tested poverty criteria—food insecurity experience, proportion of food expenditure, clothing expenditure, type of flooring, type of walls, ownership of a latrine, and source of lighting—significantly influence household poverty status. These factors serve as relevant indicators for assessing household poverty in South Sumatra. However, the employment status of the household head did not significantly impact poverty status, suggesting a need for a reevaluation of this criterion. This study provides critical insights for refining poverty measurement criteria and informing poverty alleviation policies.